ЭСХАТОЛОГИЧЕСКИЕ МОТИВЫ В ТВОРЧЕСТВЕ С.БУЛГАКОВА - ШАПОВАЛ, Н. В. (Вісник Харківського національного університету імені В. Н. Каразіна. Серія «Теорія культури і філософія науки», 2015)
В статье «Эсхатологические мотивы в творчестве С.Булгакова»рассматриваются вопросы, касающиеся соотношения тварного и божественного начал,их специфической роли в окончательном сотворении мира. Автором проанализированаприрода Булгаковского понимания ада как закономерного следствия впадения тварнойсвободы в произвол.Шаповал Н.В. ЕСХАТОЛОГІЧНІ МОТИВИ У ТВОРЧОСТІ С. БУЛГАКОВА Встатті «Есхатологічні мотиви у творчості С. Булгакова» розглядаютьсяпитання щодо співвідношення тварного і божественного начал, їх специфічної ролі востаточному створенні світу. Автором здійснений аналіз Булгаковського розуміння пеклаяк закономірного наслідку перетворення тварної свободи у свавілля.Ключові слова: вічність, тимчасовість, необхідність, тварна свобода, пекло.Shapoval N.V. ESCHATOLOGICAL MOTIVES AT S. BULGAKOV’S CREATIVITY Thearticle «Eschatological motives at S. Bulgakov’s creativity» points out some questions,connecting with the correlation between created and divine bases, theirs specific function in thefinal creation of the universe. Author expounds an interrelationship between eternity andtemporary, as the last one is no other than eternity, stretching into the being and foldingnothingness by creative way. Eternity grounds temporary, it is transcendental against temporaryand needs nothing for itself. God as a creator of the universe present himself a presence eternityin temporary. It was payed attention to “cooperation” between the Supreme Being and allcreation, while created liberty was assumed. The universe finds its final creation with matchingof created liberty and necessity, divine and human bases only. God willing doesn’t influence onthe universe mechanically but by creative way, always according to the decision and action ofcreated liberty for the best advantage of all creation. The creation is also the dispensation aboutcreatures, the Lord Almighty is the Sustainer too. It isn’t the dispensation of capricious and selfwilleddespot but a paternal unmercenary care. There is no pre-establishment in the world’sactivity or people’s lives. Created liberty chooses and actualizes one probability from itsindefinite variety. The Hand of the Sustainer is visible for ordinary person at the exclusivemoments and only the Saints and Enlighteneds realize the world as a consistent miracle.Author also has reviewed the nature of Bulgakov’s comprehension of the hell as a naturaleffect of created liberty, which felt into the arbitrariness. Aspect, which is concerning a hell aspotential but not obligatory ontological effect of the action of created liberty, is cleared out. Hellgrows from the no volition of the good and disagreement between real and subjective in thehuman nature. Hell like an evil doesn’t have ontological existence. They are called thehallucinations, naturally appearing in the perverted souls. As God had accepted human libertyin corpora, it is indispensable to consider with all its outcomes even if they brings hellishagonies. They are an opposite side of the liberty. God’s respect to the liberty declares itself justin these agonies. No one may be saved by the forcible way. Therefore God’s forgiveness is notenough for it, an availability to take the forgiveness is necessary too, it is called a repentance.More over the hellish agonies aren’t applies on people but choose by themselves. So there is aprobability to overcome it with the same human self, who has given birth to it.Key words: eternity, temporary, necessity, created liberty, hell.